2022
DOI: 10.3389/fpsyt.2022.990994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive behavioral therapy on improving depressive symptoms and increasing adherence to antiretroviral medication in people with HIV

Abstract: The incidence of depression is higher in PLWH (people living with HIV) than in the general population. It is of clinical significance to explore effective measures to improve depression in patients. But the available evidence is still quite limited. CBT (cognitive behavioral therapy) is considered to be one of the effective methods to improve depression, medication adherence and quality of life in PLWH. Therefore, this study aimed to systematically evaluate the effect of cognitive behavioral therapy on improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Firstly, in our study, most subjects showed cooperativeness and even interest in filling up questionnaires and complying to follow ups, differing from results in research by Gutiérrez-Veililla and collaborators [14]. Another difference found in our investigation from others, is that there's a well-documented association of age progression and the development of depressive episodes in PLWHIV, due to psychosocial, virulent and neurohormonal factors [23]. However, in our study, this association was not found, and to the contrary, negative correlation was found.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Firstly, in our study, most subjects showed cooperativeness and even interest in filling up questionnaires and complying to follow ups, differing from results in research by Gutiérrez-Veililla and collaborators [14]. Another difference found in our investigation from others, is that there's a well-documented association of age progression and the development of depressive episodes in PLWHIV, due to psychosocial, virulent and neurohormonal factors [23]. However, in our study, this association was not found, and to the contrary, negative correlation was found.…”
Section: Discussioncontrasting
confidence: 97%
“…Depression has a relation with treatment non-adherence behavior [23]. This was also seen in our results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The intervention model consisted of psychoeducation, Behavioural Activation, antidepressant medication and referral to mental health workers; delivered in a stepped care fashion. The therapies have previously been shown to be effective against depression in primary care settings including in HIV care [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%